Insulin delivery devices 100 years on. (2nd August 2021) - Sharp, Patrick; Ives, Emma
Abstract: The extraction of insulin from the pancreas and its subsequent use in the treatment of diabetes presented a new set of problems. Of these, insulin delivery is perhaps so obvious that it does not get the attention it deserves. Syringes dedicated to the delivery of insulin made minor progress for the first 60 years but the development of the pen injector from the 1980s onward has been fertile ground for innovation. Near field connectivity in various forms continues to push the boundaries. In the background, there is slow progress on development of non‐injectable delivery modalities. Copyright © 2021 John Wiley & Sons.